The Modularity Theorem Jerry Shurman Y + Xy + Y = X − X − X − 14 −1, 0, −2, 4, 0, −2, 1, −4, 4, 6, 4,
The Modularity Theorem Jerry Shurman y2 + xy + y = x3 − x2 − x − 14 −1, 0, −2, 4, 0, −2, 1, −4, 4, 6, 4, . This talk discusses a result called the Modu- larity Theorem: All rational elliptic curves arise from modular forms. Taniyama first suggested in the 1950’s that a statement along these lines might be true, and a precise conjecture was formulated by Shimura. A 1967 paper of Weil provides strong theoretical evidence for the conjecture. The theorem was proved in the mid-1990’s for a large class of elliptic curves by Wiles with a key ingredient supplied by joint work with Taylor, completing the proof of Fermat’s Last The- orem after some 350 years. The Modularity Theorem was proved completely around 2000 by Breuil, Conrad, Diamond, and Taylor. I. A Motivating Example For any d ∈ Z, d 6= 0, consider a quadratic equation, Q : x2 − dy2 = 1. For any prime p not dividing 2d, let Q(Fp) de- note the solutions (x,y) of Q working over the e field Fp of p elements, i.e., working modulo p. Since we expect roughly p solutions, define a normalized solution-count ap(Q)= p −|Q(Fp)|. There is a bijective correspondencee 1 2 P (Fp) \{t : dt = 1} ←→ Q(Fp). Specifically (exercise), the map ine one direc- tion is 1+ dt2 2t t 7→ , , ∞ 7→ (−1, 0) 1 − dt2 1 − dt2! and the map in the other direction is y (x,y) 7→ , (−1, 0) 7→ ∞. x + 1 1 2 But the set P (Fp) \ {t : dt = 1} contains p − 1 elements or p + 1 elements depending on whether d is a square modulo p or not.
[Show full text]